Experimental study on production characteristics and enhanced oil recovery during imbibition and huff-n-puff injection in shale reservoir - Jianguang Wei; Demiao Shang; Xiaoqing Zhao; Xiaofeng Zhou; Yang, Ying; Meng Du (Capillarity, 2024)
Imbibition and huff-n-puff injection in shale reservoirs can significantly enhance oil recovery after depletion. To clarify the microscopic production characteristics and enhance the oil recovery mechanisms across different pore scales during imbibition and huff-n-puff injection, this study establishes an online physical simulation method that integrates imbibition and huff-n-puff using nuclear magnetic resonance and conducts a series of online nuclear magnetic resonance analyses under different imbibition systems. The microscopic production characteristics and dynamic development characteristics are quantitatively studied from the aspects of pore recovery and residual oil distribution. The results show that the occurrence states of pores of shale oil can be categorized into three types, including adsorption pore as the predominant type, followed by percolation pore and migration pore. When viewing the entire imbibition process comprehensively, it becomes imperative to maximize the recovery of migration pores while ensuring the recovery degree of adsorption pores. The recovery of free oil increases with the imbibition amount and the residual oil gradually shifts to adsorbed and organic matter-dominated forms, resulting in gradually decreasing recoverability. Using water-based imbibition media achieves a superior production effect for adsorbed oil in interlayered clay, whereas CO2 imbibition media can effectively improve the recovery of organic matter through mass transfer, leading to 11.01%-23.54% enhancement in oil recovery. Leveraging the bridge flow conductivity of fractures, fluid imbibition displacement and CO2 carrying effect emerges as a pivotal strategy for achieving optimal enhanced oil recovery. Document Type: Original article Cited as: Wei, J., Shang, D., Zhao, X., Zhou, X., Yang, Y., Du, M. Experimental study on production characteristics and enhanced oil recovery during imbibition and huff-n-puff injection in shale reservoir. Capillarity, 2024, 12(2): 41-56. https://doi.org/10.46690/capi.2024.08.02